Metabolomic analysis of extreme freezing tolerance in Siberian spruce (Picea obovata). Issue 3 (20th August 2014) - Angelcheva, Liudmila; Mishra, Yogesh; Antti, Henrik; Kjellsen, Trygve D.; Funk, Christiane; Strimbeck, Richard G.; Schröder, Wolfgang P.
Summary: Siberian spruce ( Picea obovata ) is one of several boreal conifer species that can survive at extremely low temperatures (ELTs). When fully acclimated, its tissues can survive immersion in liquid nitrogen. Relatively little is known about the biochemical and biophysical strategies of ELT survival. We profiled needle metabolites using gas chromatography coupled with mass spectrometry (GC‐MS) to explore the metabolic changes that occur during cold acclimation caused by natural temperature fluctuations. In total, 223 metabolites accumulated and 52 were depleted in fully acclimated needles compared with pre‐acclimation needles. The metabolite profiles were found to develop in four distinct phases, which are referred to as pre‐acclimation, early acclimation, late acclimation and fully acclimated. Metabolite changes associated with carbohydrate and lipid metabolism were observed, including changes associated with increased raffinose family oligosaccharide synthesis and accumulation, accumulation of sugar acids and sugar alcohols, desaturation of fatty acids, and accumulation of digalactosylglycerol. We also observed the accumulation of protein and nonprotein amino acids and polyamines that may act as compatible solutes or cryoprotectants. These results provide new insight into the mechanisms of freezing tolerance development at the metabolite level and highlight their importance in rapid acclimation to ELT in P. obovata .